Finite element analysis on tooth and periodontal stress under simulated occlusal loads. (27th April 2017) - Zhang, H.; Cui, J.‐W.; Lu, X. L.; Wang, M.‐Q.
Summary: The tooth stress elicited by occluding contact represents critical biomechanical information about dental health during chewing. Effects of occlusal contact on tooth stress remain obscure. In this study, a mandibular first molar finite element model was built from CT images. The effects of area size, location and direction of occlusal loading on both tooth and periodontal stresses were analysed. Results showed tooth and periodontal stress had drastically different patterns. Tooth stress value was much higher than periodontal stress value under the same task. Tooth stress concentration area and its value decreased from outside to inside. The Maximum Tooth Stress (MTS) always occurred at the loading site and a larger loading area elicited a smaller MTS value. The variation of MTS was larger when the fossa bottoms were inclined loaded than when the cusp tips were inclined loaded, larger when lingually loaded than when buccally loaded and larger when mesially loaded than when distally loaded. Distal loadings generally induced smaller Maximum Periodontal Stress (MPS) variations than the mesial loadings. These findings indicated exposure of the rational site(s) to occlusal contact should be helpful to achieve proper tooth and periodontal stress, thus to diminish loading associated structure problems.